Cross-cultural communication and symbolic commodification in Ubud: A Barthesian analysis of tourism myths and identity negotiation - Wilantara Made (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Cross-cultural communication in Ubud represents a critical friction point where high-context local traditions clash with low-context tourist expectations. This study investigates how cultural symbols are negotiated and transformed into tourism myths within this ecosystem. Employing an interpretive qualitative approach, data was collected through in-depth interviews with six key informants representing local and tourist perspectives, alongside participant observation in ritual and commercial spaces. The analysis was operationalized using Roland Barthes’ semiotic framework to trace the shift from denotation to myth. Findings reveal a systematic recoding of signifiers where local denotations, such as dance as a sacred offering or yoga as a modern lifestyle, are overwritten by tourist connotations of exotic magic and ancient spirituality. These individual perceptions coalesce into a second-order signification system, producing the global "Myth of Paradise." This myth functions to naturalize the commodification of culture, where authenticity becomes a negotiated service rather than an inherent quality. The study concludes that the "Paradise" narrative actively masks sustainability challenges, suggesting that future tourism management must prioritize cultural literacy over myth-making to ensure community resilience.